Saberes e fazeres quilombolas : um olhar sobre as práticas pedagógicas da área de ciências humanas da escola de Mata-Cavalo - Santana, Gonçalina Eva Almeida de (2019)
This study is the result of qualitative research of an ethnographic nature realized at State School Professor Tereza Conceição Arruda, located at Quilombo Mata-Cavalo/Nossa Senhora do Livramento-MT. The objective of this study was to understand the pedagogical practices used by teachers of the Human Sciences area at the mentioned school, with focus in the observation of the process of articulation of scientific knowledge and traditional quilombola knowledge in its social, historical and cultural contexts. In addition, it discusses the Public Policies related to the modality of Quilombola School Education and presents the historical struggle of the matacavalenses for formal education. The theoretical foundation is anchored in Castilho (2011), André (1995), Geertz (1989), Minayo (2008), Denzin and Lincoln (2006), Bardin (1979), Hall (2006), Munanga Barth (1998), Freitas (1978), Moura (1988, 2001), O'Dwyer (2002), Silva (2014), Bandeira (1992), Barros (2007), Nunes (2001), Freire (2016) and others. The instruments used to collect data were: participant observation, semi-structured interview, life story, field diary record, documents and photographs. Efforts on the part of the teachers, in order to carry out an education contextualized with the community reality, articulated with the scientific knowledge, despite the adverse conditions in terms of infrastructure, financial resources and pedagogic materials, was showed as results. It is identified that teachers are ourselves organized to seek training for the improvement of quilombola pedagogy. Besides that, it is also noticed that the materializations of the public policies for Quilombola School Education are moving in timid steps, without dialogue and no secure decent conditions of work and continuous formation, jeopardizing the development of quilombola didactics, thus contradicting what is regulated in the official documents, which guide the work in schools inserted in the quilombolas territories.